Simultaneous film temperature and film thickness measurements for jet impingement applications using two-color laser-induced fluorescence - Koegl, Matthias; Mil‘to, Nikita; Zigan, Lars (Experiments in Fluids, 2024)
The study investigates a jet impingement cooling process of a cylindrical geometry relevant for electric and electronic applications. The applied two-color detection technique enables a simultaneous determination of film temperature and film thickness. For this purpose, the heat transfer oil Marlotherm LH was doped with the temperature-sensitive fluorescence tracer nile red. The temperature determination was realized by suitable band pass filters. Preliminary spectral investigations were carried out in terms of varying dye concentration, temperature and film thickness. At high dye concentrations (up to 37.5 mg/L), reabsorption effects lead to a spectral shift toward higher wavelengths with increasing film thickness. Low dye concentrations (0.29 mg/L, 0.59 mg/L) show no film thickness dependent spectral shift. A film temperature investigation at low dye concentration showed no bias of the intensity ratio due to film thickness, i.e., no additional spectral shift toward lower wavelengths was observed. The investigations on the jet impingement setup revealed an increasing film temperature and decreasing film thickness with increasing solid temperature. The average film temperature increases with increasing solid temperature from 298 (solid temperature 298 K) to 308 K (solid temperature 398 K). At higher solid temperatures, the film temperature increases with distance to the stagnation zone. The average film thickness decreases with increasing solid temperature from 0.24 to 0.17 mm. At high solid temperatures, the film temperature increased with radial distance to the stagnation zone. This behavior is caused by the increasing temperature gradient with increasing solid temperature and decreasing viscosity with increasing film temperature.
CRIS-Team Scopus Importer:2025-02-04